An asymmetry of translational biological motion perception in schizophrenia - Hastings, Caitlin; Brittain, Philip; ffytche, Dominic (Frontiers in Psychology, 2013)
Background Biological motion perception is served by a network of regions in the occipital, posterior temporal and parietal lobe, overlapping areas of reduced cortical volume in schizophrenia. The atrophy in these regions is assumed to account for deficits in biological motion perception described in schizophrenia but it is unknown whether the asymmetry of atrophy described in previous studies has a perceptual correlate. Here we look for possible differences in sensitivity to leftwards and rightwards translation of point-light biological motion in data collected for a previous study and explore its underlying neurobiology using functional imaging. Methods n=64 patients with schizophrenia and n=64 controls performed a task requiring the detection of leftward or rightward biological motion using a standard psychophysical staircase procedure. 6 control subjects took part in the functional imaging experiment. Results We found a deficit of leftward but not rightward biological motion (leftward biological motion % accuracy patients = 57.9%±14.3; controls = 63.6%±11.3 p=0.01; rightward biological motion patients = 62.7%±12.4; controls = 64.1%±11.7; p>0.05). The deficit reflected differences in distribution of leftward and rightward accuracy bias in the two populations. Directional bias correlated with functional outcome as measured by the Role Functioning Scale in the patient group when co-varying for negative symptoms (r=-0.272, p=0.016). Cortical regions with preferential activation for leftwards or rightwards translation were identified in both hemispheres suggesting the psychophysical findings could not be accounted for by selective atrophy or functional change in one hemisphere alone. Conclusions The findings point to translational direction as a novel functional probe to help understand the underlying neural mechanisms of wider cognitive dysfunction in schizophrenia.